THE METHOD OF INTERPRETATION ON QS. AL-FATIHAH IN TARJUMAN AL-MUSTAFID BY ABDUL RAUF AS-SINGKILI - Wendi Parwanto; Taufik Akbar; AbdulGafar Olawale Fahm (QiST: Journal of Quran and Tafseer Studies, 2022)
This study is motivated by the lack of studies on the methodological configuration of al-Fatihah's interpretation in Tarjuman al-Mustafid. Therefore, researchers are interested in conducting this study further. This type of research is library research using the primary data source of the interpretation of Tarjuman al-Mustafid by Abd Ar-Rauf As-Singkili which is focused on the interpretation of al-Fatihah. The method used is a descriptive-analytical method. The conclusion of this article explains that: First, the Systematic Interpretation of As-Singkili is explaining the Makkiyah or Madaniyah letter, explaining the benefits of the letter and its asbab an-nuzul, writing the text of the verse without translation, and then doing the interpretation. Second, the source of interpretation uses munasabah, hadith, and scholars' arguments (quotations from other interpretations). Third, the principles of interpretation are 1) the Principles of Letter Description; 2) The Qiraat Accentuation Principle; 3) the Principles of Global-Parochial Interpretation; and 4) the Principles of Textual Interpretation. Fourth, the Caustive-Axiological interpretation carried out by As-Singkili in interpreting al-Fatihah emphasizes the socio-cultural aspect and minimizes differences of opinion in reading (qiraat) on the verse malikiyaumiddin.